The vital cog of e-tutorship in Open, Distance and e-Learning facilitation : a phenomenological study - Mashile, Elias Oupa (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Electronic tutorials (e-tutorials) are an integral part of student support in Open Distance and e-Learning and influence students’ learning experience, motivation, and retention. Continual developments in online education and challenges encountered by education participants in resource constrained environments raise a need to conduct more research to better understand the phenomenon of e-tutoring (electronic tutoring) and its improvement. This study used a hermeneutic phenomenological approach to understand the lived experiences of electronic tutors (e-tutors) in a large Open Distance and e-Learning institution in South Africa. Data collection occurred through six semi-structured focus group interviews. The data was then subjected to a thematic analysis and presented through the lens of the Community of Inquiry model. The findings indicate that although e-tutors provide facilitation of learning, technical support, managerial activities, and social integration to foster teaching presence, cognitive presence, and social presence, not all students were able to participate. Furthermore, the conditions necessary to foster cognitive presence were non-optimal. Recommendations are the broadening of e-tutorials to include all students as well as conducting more research on how to enhance cognitive presence in online courses offered by institutions in developing nations.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL Vol. 7 (3) (2023)
Keywords: Online Learning; Electronic tutorship; Electronic tutors; Open distance and eLearning; Community of Inquiry; Computer-assisted instruction; Distance education; Open learning